ANGIOSARCOMA OF THE HEART - Harris, Hilda R. (1960)
The clinical features and pathological details of a primary cardiac angiosarcoma are described. The significance of the various clinical manifestations of primary cardiac tumours is discussed. The incidence, the histological diagnosis, and the histogenesis of primary cardiac angiosarcoma are considered.